The Usefulness of Quantitative EEG and Advanced MR Techniques in the Monitoring and Long-Term Prognosis of Lance-Adams Syndrome - Szczepańska, Aleksandra; Dziadkowiak, Edyta; Bladowska, Joanna; Kipiński, Lech; Budrewicz, Sławomir; Koszewicz, Magdalena (Frontiers in Neurology, 2019)
Objectives: Chronic post-hypoxic myoclonus, known as Lance-Adams syndrome, is a rare complication of successful cardiopulmanary resuscitation. It is characterized by intention myoclonus, cerebellar ataxia and preserved intellect. The basis of the disease and its long-term prognosis remain unclear. Case report: The authors present a 53-year-old woman with a history of asthma bronchiale who suffered from myoclonus after hypoxic brain damage due to cardiac arrest Advanced electrophysiological (quantitative EEG) and MR (MR spectroscopy) techniques were employed. Conclusions: Over long-term observation the results suggested permanent synaptic rearrangements of the neuronal networks due to brain plasticity in the patient after the brain hypoxia.